2021
DOI: 10.3390/pathogens10070875
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Patterns on H. pylori Infection and the Modulation of Microbiota to Counteract Its Effect. A Narrative Review

Abstract: Helicobacter pylori (H. pylori) is a Gram-negative bacterium that colonizes the stomach and can induce gastric disease and intra-gastric lesions, including chronic gastritis, peptic ulcers, gastric adenocarcinoma, and mucosa-associated lymphoid tissue lymphoma. This bacterium is responsible for long-term complications of gastric disease. The conjunction of host genetics, immune response, bacterial virulence expression, diet, micronutrient availability, and microbiome structure influence the disease outcomes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 123 publications
1
8
0
Order By: Relevance
“…Similar to our findings, a large-scale cross-sectional survey found that a diet characterized by a large intake of animal viscera, animal blood, fish, seafood, and poultry was associated with a reduction in the rate of H. pylori infection 25. Many substances ingested in the diet have strong antibacterial activity against H. pylori and change the gastric environment through the nutritional intake of the host, which may reduce the possibility of its colonization 26…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our findings, a large-scale cross-sectional survey found that a diet characterized by a large intake of animal viscera, animal blood, fish, seafood, and poultry was associated with a reduction in the rate of H. pylori infection 25. Many substances ingested in the diet have strong antibacterial activity against H. pylori and change the gastric environment through the nutritional intake of the host, which may reduce the possibility of its colonization 26…”
Section: Discussionsupporting
confidence: 87%
“…25 Many substances ingested in the diet have strong antibacterial activity against H. pylori and change the gastric environment through the nutritional intake of the host, which may reduce the possibility of its colonization. 26 The prevalence of H. pylori in China was the highest in the west, followed by the eastern coastal regions, and the lowest in the central region. The spatial trend analysis module was used to draw the disease trend map in 3-dimensional space to reflect the overall changes of the disease in latitude and longitude.…”
Section: Discussionmentioning
confidence: 98%
“…It is known that the mechanism of action of a number of probiotic strains on H. pylori is due to the production of peptides and non-peptide substances that inhibit the growth and adhesion of the pathogenic strain [5,17,18]. Probiotics are known to inhibit H. pylori attachment to human gastric epithelial cell lines, suppress the inflammatory processes associated with this infection, and inhibit the growth of antibiotic-resistant H. pylori [19]. The probiotic microorganisms release antibacterial compounds and shortchain fatty acids, which inhibit the growth of H. pylori bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic H. pylori infection-related disease outcomes are influenced by the interaction of host genetics, immunological response, bacterial virulence expression, diet, availability of micronutrients, and microbiome structure. The burden of CG is therefore compounded due to poor diets [4]. usually present with abdominal pain in the epigastric region which might mostly be accompanied by a burning sensation and loss of appetite.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic H. pylori infection-related disease outcomes are influenced by the interaction of host genetics, immunological response, bacterial virulence expression, diet, availability of micronutrients, and microbiome structure. The burden of CG is therefore compounded due to poor diets [ 4 ].…”
Section: Introductionmentioning
confidence: 99%